30 heritage buildings of Yangon inside the city that captured time - Rooney, Sarah 1970-; Association of Myanmar Architects (Chicago Serindia Publications, 2012)
"This volume is a compilation of 30 important colonial-era buildings in Yangon, Myanmar. It provides the history of each building and is illustrated with both present and old photographs"--Provided by publisher.
"[Published in association with] Association of Myanmar Architects."
Includes bibliographical references (p. 156-157) and index.
Keywords: Architecture -- Burma -- Rangoon -- History; Architecture -- Conservation and restoration -- Burma -- Rangoon; Rangoon (Burma) -- Buildings, structures, etc